2020
DOI: 10.18203/2320-1770.ijrcog20203330
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal semen parameters among males in infertile couples: a cross sectional study from a tertiary care centre

Abstract: Background: In India, the prevalence of primary infertility ranges from 3.9% to 16.8%. Male factor contributes 40-50% of this. Male factor infertility is indicated by decreased sperm concentration, reduced motility, vitality or abnormal sperm morphology. Semen analysis is the single most important investigation to detect male factor infertility. The aim of this study was to analyse the prevalence of abnormal semen parameters among males in infertile couples and their association with contributing factors.Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 11 publications
(15 reference statements)
1
0
0
Order By: Relevance
“…14,15 Association of oligospermia with increased morphological abnormalities has been suggested by Butt et.al. 16 Poor motility (Asthenozoospermia) was the single factor common abnormality found in this study constituting 25.5% which was in concordance with the study was conducted by Garg J et al 17 , Bodal et al 18 , Ugbaoja et al 19 and that reported the prevalence of asthenozoospermia 14.3%,17%, and 16.5 %respectively. However, a low percentage of asthenozoospermia was found in a study conducted by Aulia et al (5.9%) 20 and Diallo et al (10%).…”
Section: Discussionsupporting
confidence: 90%
“…14,15 Association of oligospermia with increased morphological abnormalities has been suggested by Butt et.al. 16 Poor motility (Asthenozoospermia) was the single factor common abnormality found in this study constituting 25.5% which was in concordance with the study was conducted by Garg J et al 17 , Bodal et al 18 , Ugbaoja et al 19 and that reported the prevalence of asthenozoospermia 14.3%,17%, and 16.5 %respectively. However, a low percentage of asthenozoospermia was found in a study conducted by Aulia et al (5.9%) 20 and Diallo et al (10%).…”
Section: Discussionsupporting
confidence: 90%